Neutron Yield Scaling With Inductance in Plasma Focus - Karami, Fereshteh; Roshan, Mahmud V.; Habibi, Morteza; Asadnejad, Reza; Lee, Paul; Saw, Sor Heoh; Lee, Sing (IEEE, 2015)
Neutron yield is enhanced by reduction of the short-circuit plasma focus inductance L0, which in turn increases the pinch current Ipinch. Numerical experiments are carried out to optimize the neutron production using the Lee model on small plasma focus devices (several kilojoules), such as UNU/ICTP PFF, NX2, and LDiana. The maximum neutron yield is obtained for each L0 with a combination of gas pressure as well as anode length and radius (Yn versus z0, p0 and a at fixed L0). The numerical experiments confirm the limitation effect of Ipinch, and suggest an optimum L0 in the range of 10–20 nH. Finally, the neutron yield is scaled with system inductance.